Tax allowances and their impact on income tax performance in Iraq during the period of the unjust economic blockade - محمد حسين الطويل (Iraqi Journal for Administrative Sciences, 2024)
Contemporary financial thought has settled on treating ALLAWNCES allowances within the framework of the rule of tax justice and the extent to which they take care of the principle of tax personality represented by the extent to which the taxpayer’s circumstances and the financial and social considerations surrounding him are observed. This rule occupies a prominent position among the basic rules of taxation because of its role in determining the cost estimate and determining the degree of tax pressure, which are affected by the tax measure (tax rate), tax allowances and exemptions, and the distinction in how sources of income are treated and in a way that affects the performance of the income tax. Hence the importance of It addressed the issue of allowances by defining them and their types and the development of their amounts over the period of validity of the amended Iraqi Income Tax Law No. 113 of 1982 and their impact on tax performance in Iraq during the period of the unjust economic blockade.